Gluten-free diet - opportunities and limitations - Małgorzata Sierpień; Dominika Górska; Aleksandra Karwanska; Magdalena Majcher; Agata Pikulicka; Piotr Brzychczy; Aleksandra Kulbat; Monika Majcher; Mateusz Kulbat; Kamila Świercz (Kazimierz Wielki University, 2023)
Objective  The aim of the study was to indicate the difficulties associated with gluten-free diet and the point of its use by people without medical indications. Another important aspect of the article was to analyze the impact of this diet on the course of chronic diseases.  Methods  For the purposes of writing this article, the available literature was reviewed. Using keywords such as gluten, gluten-free, or diet, the database of medical publications - PubMed was searched.  Results: The popularity of the gluten-free diet is growing. The reason for this is increased interest in health lifestyle and nutrition as well as the influence of the mass media. Because of that, the number of people on a gluten-free diet without medical indications is increasing. Following a gluten-free diet is associated with many difficulties. Gluten-free products are much more expensive and less available than their gluten-containing counterparts. It is associated with many obstacles in everyday life. An important aspect is also the imbalance of supplied nutrients and the risk of macro and micronutrient deficiencies, such as magnesium, zinc or selenium, as a result of the gluten-free diet. With the increasing popularity of the gluten-free diet, there are more and more studies on the potential benefits of its use in chronic diseases.  Conclusion: A gluten-free diet remains the only therapeutic option in the course of diseases such as celiac disease, non-celiac gluten sensitivity or wheat allergy. Due to the insufficient amount of data, its use is not recommended in the course of other chronic diseases and in the population of people without medical indications.